Dementia in a Hearing-impaired Population According to Hearing Aid Use: A Nationwide Population-based Study in Korea. Issue 6 (8th June 2022) - Byun, Hayoung; Chung, Jae Ho; Lee, Seung Hwan; Kim, Eun Mi; Kim, Inah
Abstract : Background: Hearing loss is considered a potentially modifiable risk factor for dementia. However, the effect of use of a hearing aid on the development of dementia has not been clearly established. We aimed to assess the incidence of dementia in hearing-impaired individuals according to hearing aid use in a nationwide population-based cohort study with matched controls. Methods: This was a retrospective, longitudinal, cohort study of South Korean national claims data for individuals newly registered with hearing disabilities (better ear ≥40 dBHL with worse ear ≥80 dBHL, or better ear ≥60 dBHL) between 2004 and 2008. The hearing aid cohort comprised individuals who received hearing aid subsidies from the National Health Insurance within a year from disability registration. The comparison cohort comprised individuals without a record of a hearing aid claim during the study period after 1:1 matching for audiologic and sociodemographic factors with the hearing aid cohort. The occurrence of dementia was followed up until 2018. Results: Each cohort comprised 8780 individuals. Overall incidence of dementia in the hearing aid and comparison cohorts were 156.0 and 184.5 per 10, 000 person-years, respectively (incidence rate ratio = 0.85, 95% confidence interval 0.79–0.91). In a multivariable analysis of the whole study populations, hearing aid use (hazard ratio = 0.75, 95% confidence interval 0.70–0.81) attenuated the risk of dementia. Conclusions: Dementia incidence in individuals with hearing disabilities was lower in hearing aid users than that in nonusers. Hearing rehabilitation with hearing aids should be encouraged for individuals with hearing loss.